Systematic Review Using Neutrosophic Torgerson and Neutrosophic Vader to Determine the Impact of Mobile Applications in the Labor Integration of Disabled People. - Gamboa-Cruzado, J. (2023)
People with a disability are the most likely to end up unemployed. Knowing and finding new ways to integrate them into society is urgent in an increasingly dynamic and versatile world. The systematic Review of the literature (SRL) was developed covering the issue of labor integration of people with disabilities.. The main objective of the research was to determine the state of the art of research on Mobile Applications and their impact on the Labor Integration of People with Disabilities. The use of relationship coefficients between two neutrosophic numbers, through the Torgerson method, Allowed the evaluation of the applications by the experts. The results obtained highlight the importance of mobile technology in the process of ensuring that people with disabilities find the desired job, in addition, accessibility must be met for the correct development of the application for the various existing disabilities. By utilizing Neutro-VADER and Neutrosophy, the precision and efficiency of sentiment analysis are enhanced, especially when handling uncertain or unclear text and consulting with experts. By implementing a more intricate and refined sentiment analysis method, these tools can generate more practical and valuable perspectives regarding the sentiment of written or spoken language.